2016
DOI: 10.1007/s10072-016-2622-x
|View full text |Cite
|
Sign up to set email alerts
|

Event-related potentials and cognitive performance in multiple sclerosis patients with fatigue

Abstract: The aim of this study was to evaluate event-related potentials (ERP) and cognition in multiple sclerosis (MS) patients with regard to fatigue and disease-related variables. The study comprised 86 MS patients and 40 controls. Fatigue was assessed using the Fatigue Severity Scale (FSS/FSS-5) and the Modified Fatigue Impact Scale (MFIS/MFISmod). N200 and P300 components of auditory ERP were analyzed. Cognition was evaluated by means of Brief Repeatable Battery of Neuropsychological Tests (BRBNT). The results of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…In a similar manner, cognitive measures were the subject of some studies. While some studies have found a correlation between self-reported fatigue and each of attention [80,165], memory [165] and information processing speed [3,142]; others failed to detect such a relationship [5,158,194]. The discrepancy in these findings might lie in the difference among the trials in terms of chosen cohorts and/or employed motor/cognitive tasks (e.g.…”
Section: Objective Measuresmentioning
confidence: 84%
“…In a similar manner, cognitive measures were the subject of some studies. While some studies have found a correlation between self-reported fatigue and each of attention [80,165], memory [165] and information processing speed [3,142]; others failed to detect such a relationship [5,158,194]. The discrepancy in these findings might lie in the difference among the trials in terms of chosen cohorts and/or employed motor/cognitive tasks (e.g.…”
Section: Objective Measuresmentioning
confidence: 84%
“…[29][30][31] Relationships between ERP parameters and the duration of the disease or the degree of disability were more disputable. 27,28,32 Sundgren et al pointed to the prognostic importance of the P300 parameters. 33 They noted that the progression of cognitive disorders was accompanied by an increased latency and decreased amplitude of the P300 wave.…”
Section: Discussionmentioning
confidence: 99%
“…ERPs also provide non-invasive neurophysiological measurements with high temporal resolution, allowing to assess dysfunctional brain dynamics, including cognitive processes that may not be apparent at the behavioral level (Woodman, 2010;Sanei and Chambers, 2013). Indeed, ERPs are commonly used clinically in neurophysiological diagnostic units to support the assessment of neuropsychiatric disorders [e.g., multiple sclerosis (Pokryszko-Dragan et al, 2016)] and sensory disorders [e.g., screening of neonates for hearing impairments (Paulraj et al, 2015)].…”
Section: Introductionmentioning
confidence: 99%